Deciding on the most suitable teaching method in the mathematics classroom - Serin, Hamdi (Opción, 2019)
In this research conducted with 35 mathematics teachersselected by stratified co-probative sampling method, the use ofteaching methods/approaches and techniques that mathematicsteachers used in their lectures were examined and tried to determinetheir opinions about the application in mathematics teaching. As aresult, most of the mathematics teachers who participated in theresearch do not use games, case studies and problem-solving. Inconclusion, the work of observing and rearranging the curriculumshould be based on the mental and physically active participation ofthe students in the mathematics learning process